What Makes an Air Route Profitable? Airport Presence, Low-Cost Carriers and Airline Alliances in the Deregulated European Aviation Market - Tománková, Ivana (2014)
This thesis examines the determinants of air route profitability in the European Union and the cooperating countries of Norway and Switzerland. Building on the assumption that only profitable routes are served, I develop a set of probit models that specify route service as a function of route characteristics, airline networks' attributes, airline partnerships and competition. Estimation results show that route profitability increases with population size and decreases with flight distance and the time efficiency of car travel relative to air travel. An airline's airport presence, that is, its share of airport operations, exerts a significant, positive effect on its route profitability, and so does airport presence of its group or allied partners. Competitive effects are asymmetric across airline business types. This paper's contribution to existing airline-route profitability studies lies in accounting for airline cooperation, controlling for an alternative mode of transport, and using EU data for estimation.